2016
DOI: 10.1111/add.13237
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease attributable to cannabis use in Canada in 2012

Abstract: The cannabis-attributable burden of disease in Canada in 2012 included 55,813 years of life lost due to disability, caused mainly by cannabis use disorders. Although the cannabis-attributable burden of disease was substantial, it was much lower compared with other commonly used legal and illegal substances. Moreover, the evidence base for cannabis-attributable harms was smaller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 62 publications
0
64
0
2
Order By: Relevance
“…8 A study conducted in 2012 on the burden of disease that is attributable to marijuana use in Canada showed that, if only nonsmoked forms of marijuana were consumed, at least two-thirds of deaths attributable to marijuana use that year would have been avoided. 9 For the most part, smoking is no longer normal owing to many years of tobacco control. However, public acceptability of smoking may change again if marijuana is legalized.…”
Section: Key Pointsmentioning
confidence: 99%
“…8 A study conducted in 2012 on the burden of disease that is attributable to marijuana use in Canada showed that, if only nonsmoked forms of marijuana were consumed, at least two-thirds of deaths attributable to marijuana use that year would have been avoided. 9 For the most part, smoking is no longer normal owing to many years of tobacco control. However, public acceptability of smoking may change again if marijuana is legalized.…”
Section: Key Pointsmentioning
confidence: 99%
“…Sameer Imtiaz and colleagues have used the methods developed as part of the 2010 Global Burden of Disease Comparative Risk Assessment to estimate the contribution that cannabis use made to the burden of disease (BoD) in 2012 in Canada, a developed country where the prevalence of cannabis use is among the highest in the world [1].…”
Section: Commentary On Imtiaz Et Al (2016): the Burden Of Disease Atmentioning
confidence: 99%
“…
Commentary on Imtiaz et al (2016): The burden of disease attributable to cannabis-implications for policyThe contribution that current patterns of cannabis use make to the burden of disease is very useful information, but it cannot decide policy.Sameer Imtiaz and colleagues have used the methods developed as part of the 2010 Global Burden of Disease Comparative Risk Assessment to estimate the contribution that cannabis use made to the burden of disease (BoD) in 2012 in Canada, a developed country where the prevalence of cannabis use is among the highest in the world [1].They included among the cannabis-related causes of disease burden: cannabis use disorders (CUD), road traffic injuries and deaths, schizophrenia and lung cancer. CUD are a consequence of cannabis use by definition; recent meta-analyses suggest that cannabis use modestly increases the risk of road traffic injuries and deaths, and there is reasonable evidence that regular cannabis is a contributory cause of the onset of psychoses [2], although some argue that we cannot exclude the possibility of residual confounding [3].
…”
mentioning
confidence: 99%
“…The findings suggest that early adolescent marijuana use impairs brain development which was manifested in impairments in reaction time and attention span (Ehrenreich et al, 1999). Long term use of marijuana has been associated with negative physiological conditions such as lung cancer and schizophrenia triggered by extensive marijuana use (Imtiaz et al, 2016). Utilizing life expectancy estimates, calculations were performed based on the age and number of adverse life-altering events attributed to marijuana use.…”
Section: Consequences Of Marijuana Usementioning
confidence: 99%
“…Immediate physiological impacts from marijuana use include impaired driving while under the influence (Rogeberg & Elvik, 2016) and impairments in learning and memory (Grant, Gonzalez, Carey, Natarajan, & Wolfson, 2003). Long term use can lead to increased risk of lung cancer and other health risks (Imtiaz et al, 2016). Marijuana use has also been associated with negative social outcomes such as lower educational levels, less participation in social activities that don't include drug use, and fewer non-drug using relationships (Meshesha, Dennhardt, & Murphy, 2015;Patton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%